An examination of pre-service teachers' goal orientations, self-regulation and active procrastination - Taura, Ali Abdullahi; Abdullah, Maria Chong; Roslan, Samsilah; Omar, Zoharah (Marsland Press, 2014)
This study examined the relationships between intrinsic goal orientation, extrinsic goal orientation, self-regulation and active procrastination; and the mediating role of self-regulation in these relationships. A total of 426 pre-service teachers (223 males, 203 females) studying in colleges of education in Nigeria participated in the study. A set of self-report questionnaire was used to measure the participants’ levels of procrastination, goal orientations, and self-regulation. Structural equation modelling (SEM) using AMOS software was employed as statistical technique for data analysis of the study. The findings, based on the hypothesized structural model, which overall goodness-of-fit indices indicate good model fit revealed that, while extrinsic goal orientation was found to be directly significant predictor of active procrastination, intrinsic goal orientation was not. However, mediation analysis, based on SEM or modern approach, indicated that there was an evidence of indirect effects of the predictor variables on active procrastination through self-regulation. Test of mediation by bootstrapping method established significant mediating role of self-regulation in the relationships between intrinsic goal orientation and extrinsic goal orientation and active procrastination. Conclusion and implications of the study have been highlighted.